Risk-based design of electric power systems for non-conventional nuclear facilities at shutdown modes - S. S. Borsoi; D. B. Baroni; M Mattar Neto; P. S. P. Oliveira; M. C. Maturana (Brazilian Journal of Radiation Sciences)
The work presents a methodology for assessing the safety of electrical system designs for non-conventional nuclear facilities in shutdown. The methodology adopts the core damage frequency as the main risk measure to assess the different architectures of power systems in a non-conventional nuclear facility. Among the reasons is the absence of a specific regulatory basis for this type of installation. The adoption of standards for nuclear power plants by non-conventional nuclear facilities does not take into account the functional and operational particularities of these installations, imposing criteria that are often overestimated, which can even lead to an increase in the financial risk for carrying out the projects. Safety probabilistic analyzes become essential tools for the facilities design and licensing. The modeling and quantification of systems failures in charge of ensuring the nuclear safety of non-conventional nuclear facilities are carried out in the CAFTA software environment. In these studies, the analysis of electrical system configurations and their influence on the overall risk of the installation stand out.